Implementation of the 5E Learning Cycle Type Cooperative Learning Model in Islamic Religious Education Subjects - Nasrulloh, Muhammad Farid; Anisa, Umi; Umardiyah, Fitri; Zuhriawan, Muhammad Qoyum (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This research aims to evaluate the application of the 5E Learning Cycle Type Cooperative Learning Model in Islamic Religious Education learning in class VII at SMP Negeri 1 Peterongan, and assess whether this model is effective in improving students' problem solving abilities. The research method used was qualitative descriptive research using all class VII students at SMP Negeri 1 Peterongan. The research results show that the application of the 5E Learning Cycle Type Cooperative Learning Model is effective in improving students' problem solving abilities. Students who studied using this model recorded significant improvements in their problem-solving abilities and proficiency in Islamic Religious Education compared to the control group. Therefore, the 5E Learning Cycle Type Cooperative Learning Model can be used as an alternative learning model that is effective in motivating, building collaboration skills, and improving students' problem solving abilities in Islamic Religious Education subjects.